2019
DOI: 10.2134/jeq2018.05.0186
|View full text |Cite|
|
Sign up to set email alerts
|

Stream Corridor Soil Phosphorus Availability in a Forested–Agricultural Mixed Land Use Watershed

Abstract: Watershed land use affects nutrient and sediment export, particularly through streambank erosion, which can add to P export and contribute to eutrophication in downstream waterbodies. We characterized P of soils from four different land uses (32 sites) along streams in the Missisquoi River basin (Vermont, USA)—silage corn (Zea mays L.), hay meadow, emergent wetlands, and forest—and their corresponding streambanks. We measured total P (TP), pH 4.8 NH4–acetate P, degree of P saturation (DPS), and soluble P. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…With such low values, we speculate that streambank legacy sediments at our sites will likely serve as sinks for inorganic P under dry, aerobic/oxic conditions and under "typical" agricultural P stream concentrations. A similar conclusion was reached by Perillo et al (2019) for streambank sediments with low P (DPS < 21%) in the Missisquoi River basin in Vermont. Alternately, if these sediments are exposed to stream waters with extremely low P concentrations, they could also desorb and release P (Sienkiewicz, 2019).…”
Section: Author Manuscriptsupporting
confidence: 77%
See 2 more Smart Citations
“…With such low values, we speculate that streambank legacy sediments at our sites will likely serve as sinks for inorganic P under dry, aerobic/oxic conditions and under "typical" agricultural P stream concentrations. A similar conclusion was reached by Perillo et al (2019) for streambank sediments with low P (DPS < 21%) in the Missisquoi River basin in Vermont. Alternately, if these sediments are exposed to stream waters with extremely low P concentrations, they could also desorb and release P (Sienkiewicz, 2019).…”
Section: Author Manuscriptsupporting
confidence: 77%
“…Using M3-P, M3-Al, and M3-Fe values and following Sims et al (2002), we also computed the oxalate extractable Degree of Phosphorus Saturation for the sediments (DPS %). DPS % has been used to quantify the amount of "bioavailable" P in the sediments and its potential for leaching in runoff (Perillo et al, 2019;Sims et al, 2002). DPS % was computed using the equation [(M3P/(M3Al+M3Fe))+0.019]/0.0042, where all the M3 extractable values are in molar concentrations (Figure 4a in Sims et al, 2002).…”
Section: Sediment Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Arkansas, environmental threshold for water quality concern for M3P is higher at 150 mg kg −1 . When compared against these water quality thresholds, studies listed in Table 1 arrived at the same conclusion that streambank sediments (legacy and non-legacy) likely posed a low risk for P leaching under well oxygenated conditions and served as a net sink for P [36,[41][42][43]. All of the studies, however, did recognize that while P concentrations were low and most of the P was likely bound to metal hydro-oxides, this P could be released into solution due to the reductive dissolution of the oxides under anoxic conditions [44,45].…”
Section: Concentrations Of P In Streambank Legacy Sediments and Compamentioning
confidence: 98%
“…Most studies have focused on changes in P concentration with land use with little regard to how P concentrations and speciation vary between the land use and its corresponding streambank. In a previous study in the Missisquoi River and its tributaries (VT, USA), we compared four types of land use (silage corn, hay meadow, emergent wetlands, and forest) and their corresponding streambanks and found that TP, soil test P (modified Morgan-extractable), and degree of P saturation (DPS) values of streambank soils varied significantly between each land use and its corresponding streambank, with the exception of forest sites (Perillo et al, 2019). However, more information about P speciation is needed to better understand P cycling in these soils.…”
Section: Core Ideasmentioning
confidence: 99%